(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the function of derivative (connotative) meanings as indicators of culture in Uzbek and English languages. Through phraseological units, metaphors, and symbolic expressions in both languages, the historical experience, religious views, and mentality of the people are reflected. Derivative meaning refers to the secondary semantic layer of a word that goes beyond its literal meaning and is connected to the cultural and social life of a nation. Examples such as “oq fotiha,” “ko‘z tegmoq,” “black sheep,” and “green with envy” are examined to reveal their cultural meanings. A comparative analysis highlights the deep interrelation between language and culture. The article emphasizes the role of connotative units as essential tools in expressing national worldview from the perspective of linguistics and cultural linguistics.